Humanity and Trust to Increase Intention to Pay Zakah - Sudoto, Sudoto; Herianingrum, Sri; Widiastuti, Tika (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
Zakah is an important instrument in Indonesia's economic growth. This is considered important because it can mobilize owned assets for economic growth by empowering certain groups in society, however the potential of zakah in Indonesia has not been maximized optimally, so that community welfare has not yet been achieved. Empirically, the intention to give zakat is a determining factor in increasing the results of zakat collection. The aim of this research is to explore and examine how big the influence of Humanity and Trust is in increasing the intention to repay zakah. This research analyzes intentions in repay zakah. This research uses a quantitative approach with Structural Equation Modeling (SEM) techniques based on Partial Least Square (PLS) with primary muzakki data from 100 respondents. The research results show that humanity is not significant in the intention to repay zakah, but if Trust is an intervening variable, then humanity indirectly influences the intention to repay zakat very strongly. Trust is the main key in increasing zakat payments to zakah institutions.